Pengajaran Tata Bahasa dan Ejaan Bahasa Indonesia di Sekolah Dasar - Ardiana Pratiwi; Hamzah , Rahma Ashari (Jurnal Pendidikan Bahasa dan Sastra, 2025)
Learning grammar and spelling in Indonesian language subjects in elementary schools plays a crucial role in developing good, correct, and structured language skills from an early age. This teaching does not merely emphasize memorizing language rules, but rather aims to develop effective, logical, and polite communication skills. Grammar helps students understand the relationships between words and the correct sentence structure, while spelling fosters precision in writing, including the use of capital letters and punctuation. In the implementation of the Independent Curriculum, grammar and spelling materials are contextually packaged through the four language skills listening, speaking, reading, and writing so that students can apply them in everyday communication situations. However, teachers still face several obstacles such as limited engaging learning media, low student motivation, and a lack of mastery of communicative learning strategies. Innovation through digital technology, educational games, and project-based learning models can be solutions to increase student interest and understanding. Therefore, grammar and spelling instruction in elementary schools needs to be designed creatively and contextually to strengthen literacy skills and foster students' critical thinking